Anti-HIV/AIDS Drugs: An Overview - Pawar, Sonali; Waghmare, Santosh; Gawde, Bhagyashri; Kale, Pranit; Johri, Yash (Journal of Drug Delivery and Therapeutics, 2019)
Human Immunodeficiency Virus (HIV) is an enveloped virus, belonging to the viral family Retroviridae. It is a highly evolved virus which has grasped the attention of all researchers with its special features like morphology, genetics and also by its emerging nature3. The special feature of all retro viruses is the presence of an enzyme called Reverse transcriptase which plays major role in reverse transcription process4. HIV enters the host body, damages immune system and will cause life-threatening opportunistic infections finally leads to AIDS (Acquired Immunodeficiency Syndrome).Many advances have been made in the prevention of HIV transmission and management of HIV/AIDS since the virus was discovered in the early 1980s7. One of the most important discoveries has been antiretroviral treatment, which can halt the replication of HIV and ease symptoms, turning AIDS into a chronic condition instead of a rapidly terminal illness. Despite advances, HIV remains a major public health challenge. This article reviews the genus, life cycle, and transmission of HIV, as well as workplace issues surrounding the virus and the challenges of developing an HIV vaccine12. Keywords: Acquired Immunodeficiency Syndrome.